2021
DOI: 10.1029/2020ja028631
|View full text |Cite
|
Sign up to set email alerts
|

Gap Formation Around 0.5Ωe of Whistler‐Mode Waves Excited by Electron Temperature Anisotropy

Abstract: With a one‐dimensional particle‐in‐cell simulation model, we have investigated the gap formation around 0.5normalΩe of the quasi‐parallel whistler‐mode waves excited by an electron temperature anisotropy. When the frequencies of excited waves in the linear stage cross 0.5normalΩe, or when they are slightly larger than 0.5normalΩe but then drift to lower values, the Landau resonance can make the electron distribution form a beam‐like/plateau population. Such an electron distribution only slightly changes the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…This is not unexpected for the following reasons. It is now accepted that Landau damping by whistler‐mode waves plays an important role in establishing the power gap (e.g., see H. Chen et al., 2021; J. Li et al., 2019; Ratcliffe & Watt, 2017). Landau damping by whistler‐mode waves in this context requires a parallel component of the whistler‐mode wave field perturbation vector, and this can only exist if the wave normal angle is non‐zero (i.e., obliquely propagating modes with k × B 0 ≠ 0 ).…”
Section: Outline Of the Numerical Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not unexpected for the following reasons. It is now accepted that Landau damping by whistler‐mode waves plays an important role in establishing the power gap (e.g., see H. Chen et al., 2021; J. Li et al., 2019; Ratcliffe & Watt, 2017). Landau damping by whistler‐mode waves in this context requires a parallel component of the whistler‐mode wave field perturbation vector, and this can only exist if the wave normal angle is non‐zero (i.e., obliquely propagating modes with k × B 0 ≠ 0 ).…”
Section: Outline Of the Numerical Experimentsmentioning
confidence: 99%
“…This is not unexpected for the following reasons. It is now accepted that Landau damping by whistler-mode waves plays an important role in establishing the power gap (e.g., see H. Chen et al, 2021;J. Li et al, 2019;Ratcliffe & Watt, 2017).…”
Section: Outline Of the Numerical Experimentsmentioning
confidence: 99%
“…They suggested that the beam-like electrons could be resulted from the Landau resonance with quasi-parallel whistler waves, but they may be produced by other processes and provide the precondition for exciting very oblique waves. Recent studies have also proposed that the beam-like electron population plays a key role in the formation of the power gap around 0.5 ce E f for whistler mode waves (Chen et al, 2020(Chen et al, , 2021Li et al, 2019). Omura et al (2009) suggested that the whistler waves excited in the equatorial region will experience nonlinear damping around 0.5 ce E f by the beam-like electrons (the trapped electrons) due to magnetic field inhomogeneity, as they propagate to the higher latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that the beam‐like electrons could be resulted from the Landau resonance with quasi‐parallel whistler waves, but they may be produced by other processes and provide the precondition for exciting very oblique waves. Recent studies have also proposed that the beam‐like electron population plays a key role in the formation of the power gap around 0.5fce for whistler mode waves (Chen et al., 2020, 2021; Li et al., 2019). Omura et al.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the modified electron distributions can affect wave evolution. To name a few, nonparallel whistler waves can interact with the energetic electrons through Landau resonance to form a plateau in the parallel velocity distribution, which may play a key role in forming the wellknown 0.5 𝐴𝐴 𝐴𝐴𝑐𝑐𝑐𝑐 ( 𝐴𝐴 𝐴𝐴𝑐𝑐𝑐𝑐 is the equatorial electron gyrofrequency) power gap of whistler-mode chorus waves (Chen et al, 2021;. This electron distribution is also conducive to the generation and propagation of highly oblique whistler waves (Ma et al, 2017;Mourenas et al, 2015;.…”
mentioning
confidence: 99%